Jornalismo e representações sociais: perspectivas teóricas e metodológicas - Pereira Junior, Alfredo Eurico Vizeu (2008)
This paper’s goal is the establishment of links between the Representations Theory and the News Studies. It is considered that the connections between these two theories can offer theoretical possibilities for research focused on how, throughout the daily activity, journalists contribute on framing cultural, economical and political representations. In other words, investigations that consider the journalistic field as an instance of framing reality.